Massive facial keloid precipitated by chronic suppuration and mechanical skin traction: A case report - Chihena H. Banda; Owen Ngalamika; Victor M. Zuze; Alick Bwanga; Chibamba Mumba (Wiley, 2024)
Abstract Keloids are benign fibroproliferative tumours with a high recurrence rate of 20%-100%, therefore, multimodal treatment is recommended. We report the case of an exceptionally large facial keloid precipitated by a vicious cycle of chronic inflammation and mechanical skin traction and discuss the management challenges in a low resource setting. A 67‐year‐old man presented with a 10‐year history of a facial keloid that rapidly enlarged to 2,800 g in 2 years causing difficulties eating, speaking, dressing, head movements and breathing. He had multiple other smaller keloids, hypertension, HIV, and a keloid family history. Surgical excision of the keloid including the multiple sinuses and cysts of enclosed skin with growing hair found inside was performed. A posterior skin flap was used to achieve tension free closure and monthly triamcinolone injections commenced. Histology showed keloidal collagen bundles in a fibrotic background, foci of a lymphoplasmacytic infiltrate and multinucleated foreign body type giant cells consistent with chronic inflammation. CD34 and S100 immunohistochemistry were both negative, ruling out the differential diagnoses that included dermatofibroma. Recovery was uneventful and the patient was discharged after 2 weeks. Notably, radiotherapy was not available in our country. We report this unique case of an extremely large keloid to demonstrate the role of suppurative chronic inflammation and high skin tension in accelerated keloid growth. This case also highlights the severe global disparity in the availability of effective keloid treatment and the urgent need for access to radiotherapy services especially in Africa where keloid prevalence is highest.